Ceguera moral. La pérdida de sensibilidad en la modernidad liquida. - Urteaga., Eguzki (Reflexión Política, 2015)
Bauman, Z. y Donskis, L. (2015). Ceguera moral. La pérdida de sensibilidad en la modernidad liquida. Barcelona: Paidós. ISBN: 978-84-493-3103-9